Investigation of the geochemical signatures and conditions of formation of metacarbonate rocks occurring within the mamfe embayment of south-eastern nigeria (2012)
Hitherto unknown metacarbonate deposits constitute parts of the Cretaceous Mamfe embayment which straddles the border between south-eastern Nigeria and western Cameroon. The rock is characterisedby a high concentration of LOI, CaO and MgO and depleted content of various insoluble components. Assuming all the CaO and MgO content of the rock were related to calcite and dolomitephases, these two minerals would account for around 22.5 wt% and 76.3 wt% on average, respectively. Among the trace elements investigated, only Ba, Cs, Rb, Sr, Nb, Pb, Zr, Cd, Cu, Ni, U, Y andZn display concentrations beyond their detection limits. Chondrite normalised rare earth element patterns show that the rock under investigation show moderate to strong fractionation of light rareearth elements (LREEN) over heavy rare earth elements (HREEN) and distinct negative Eu anomaly. Multivariate statistical treatment and variation plots revealed several geochemical interrelationships,among which are the SiO2 - Al2O3 - K2O - TiO2 -Fe2O3 - Ba - Nb - Rb - Zr links which is associated with the rock's silicate fraction. The carbonate fraction comprises CaO, MgO, Sr, Pb and Cu. Theoverall geochemical signatures support development of the metacarbonate deposit from sedimentary carbonate materials that was deposited in a saline, shallow-marine, low-energy seawater environment.The consistency of the rock's chemical properties can be attributed to the relative stability experienced during the parent sedimentary materials' deposition.